Investigating English-Speaking Problems of Senior High School Students in Indonesia: Investigating English-Speaking Problems of Senior High School Students in Indonesia - Sabilla, Annisa Nur; Kaniadewi, Nita (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Abstract The study investigated the difficulties senior high school students encounter when speaking English, focusing on vocabulary and fluency. Data were collected from twelve 12th-grade students through observations, semi-structured interviews, and performance documentation. The findings revealed that students’ lack of vocabulary impacted sentence construction and fluency. Students also encountered significant challenges with grammar and pronunciation as they struggled to structure sentences and pronounce words correctly. Confidence issues caused by fear of mistakes and inadequate vocabulary further hampered their speaking abilities. To overcome these challenges, students used methods like engaging with English media and digital tools and practicing with proficient speakers. The study highlighted the importance of immersive learning and targeted practice in enhancing English-speaking proficiency and confidence.